Otherness in question : labyrinths of the self - Simão, Lívia Mathias; Valsiner, Jaan (Advances in cultural psychology., 2007)
This book brings to social scientists a new look at how human beings are striving towards understanding others-- and through that effort--making sense of themselves. It brings together researchers from all over the World who have suggested a set of new approaches to the basic research issue of how human beings are social beings, while being unique in their personal ways of being. Issues of social representation, communication, dialogical self, and human subjectivity are represented in this book. The book contributes to the contemporary epistemological and ethical debate about the question of otherness, and would be of interest to educationalists, sociologists, psychologists, and anthropologists. It is an invitation to the wide readership to join in this collective effort towards the construction of new conceptions about myselfothers relationships that allow for innovative understanding of various social practices and problem solving in society.